Determining VAK Learning Styles Using SAW and TOPSIS Methods - Pradana, Asep Doni; Wahyudin, Wahyudin; Putro, Budi Laksono (Journal of Artificial Intelligence and Software Engineering, 2025)
This study aims to identify the dominant learning styles of 10th grade PPLG SMKN 1 Talaga students and analyze the application of the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in supporting adaptive learning. Data were collected through the VAK (Visual, Auditory, Kinesthetic) learning style questionnaire, structured observation, and student learning outcomes. The SAW method was used to calculate the preference weights from the three data sources with the same weight (0.33). Vague or combined learning styles were further analyzed using the TOPSIS method for data normalization and grouping. The results showed that the kinesthetic learning style was dominant based on the questionnaire (56.25%) and learning outcomes (40.63%). However, observations showed that the visual learning style was more prominent (32.81%), revealing differences between measurement methods. These findings emphasize the importance of direct practice-based learning, especially for kinesthetic students. Learning media such as videos, direct practice, and visual-based modules are recommended to support learning effectiveness. This study proves that the integration of SAW and TOPSIS produces a comprehensive learning style evaluation, providing guidance for teachers in designing more adaptive learning strategies. Further research on a larger scale is needed for further validation.